Four thousand years in the Blue Nile: Paths to inequality and ways of resistance. Cuatro mil años en el Nilo Azul: Caminos a la desigualdad y vías de resistencia - Fernández, Víctor M. (Complutum, 2003)
As general conclusions of the papers of the Blue Nile Project dossier herein, some ideas are suggested about the prehistoric societies investigated by Spanish archaeologists in Central Sudan during the 1990’s. The project included a survey of the Wadi Soba-El Hasib region east of Khartoum and excavations of two Mesolithic sites and one Neolithic site in the Wadi Soba area. Data from different sources are combined in an attempt to construct a historical narrative. Vestiges of some cultural hiatuses were noticed in the region, namely at the beginning and the end of the Mesolithic period, the latter involving the emergence of social stratification and the decline of women status. The archaeological gap at the end of the Neolithic period is interpreted as being a consequence of hindrance to social division. Early cultures of resistance and population movements towards the Ethiopian escarpment as a refuge area are proposed as longue duréeprocesses among Nilo-Saharans of the Eastern Sahel.